Characterization of SARS‐CoV‐2 and common cold coronavirus‐specific T‐cell responses in MIS‐C and Kawasaki disease children. Issue 1 (27th October 2021) - Hsieh, Li‐En; Grifoni, Alba; Sidney, John; Shimizu, Chisato; Shike, Hiroko; Ramchandar, Nanda; Moreno, Elizabeth; Tremoulet, Adriana H.; Burns, Jane C.; Franco, Alessandra
Abstract: The immunopathogenesis of multisystem inflammatory syndrome (MIS‐C) in children that may follow exposure to SARS‐CoV‐2 is incompletely understood. Here, we studied SARS‐CoV‐2‐specific T cells in MIS‐C, Kawasaki disease (KD), and SARS‐CoV‐2 convalescent controls using peptide pools derived from SARS‐CoV‐2 spike or nonspike proteins, and common cold coronaviruses (CCC). Coordinated CD4+ and CD8+ SARS‐CoV‐2‐specific T cells were detected in five MIS‐C subjects with cross‐reactivity to CCC. CD4+ and CD8+ T‐cell responses alone were documented in three and one subjects, respectively. T‐cell specificities in MIS‐C did not correlate with disease severity and were similar to SARS‐CoV‐2 convalescent controls. T‐cell memory and cross‐reactivity to CCC in MIS‐C and SARS‐CoV‐2 convalescent controls were also similar. The chemokine receptor CCR6, but not CCR9, was highly expressed on SARS‐CoV‐2‐specific CD4+ but not on CD8+ T cells. Only two of 10 KD subjects showed a T‐cell response to CCC. Enumeration of myeloid APCs revealed low cell precursors in MIS‐C subjects compared to KD. In summary, children with MIS‐C mount a normal T‐cell response to SARS‐CoV‐2 with no apparent relationship to antecedent CCC exposure. Low numbers of tolerogenic myeloid DCs may impair their anti‐inflammatory response. Abstract : T cells derived from children with multisystem inflammatory syndrome (MIS‐C) respond to SARS‐CoV‐2 spike and nonspike peptide megapools. SARS‐CoV‐2‐specific memory T cells and homing receptors showed different patterns between CD4+ and CD8+ T cells. MIS‐C subjects had very low myeloid dendritic cells in circulation including ILT‐4+ CD4+ tolerogenic dendritic cells.